Strategic Management Accounting Techniques and Their Role in Enhancing the Market Share of Private Banks Operating in Baghdad - Ali Naser Alwan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine strategic management accounting practices and their influence on increasing the market share of private banks based in Baghdad. In order to achieve the objectives of the current research, the researcher followed the steps of the descriptive analytical method as an approach to the current research through a sample of workers in private banks amounting to (137), according to a set of variables. In order to collect the necessary data and information, a questionnaire was designed consisting of three parts, the first about demographic variables and the second. On strategic management accounting techniques and the third on market share. After applying the current research tool, the study reached the following results: 1-There is a high level of use and employment of strategic management accounting techniques in private banks operating in Baghdad?, 2- There is a good level of market share for private banks in Baghdad, 3-There is no effect of the two techniques (activity-based costing and target costing) in enhancing the market share of private banks in Baghdad.4- The use of benchmarking techniques has an impact on improving the market share of private banks operating in Baghdad.